Addressing the challenge for expedient ethical review of research in disasters and disease outbreaks. (4th December 2018) - Aarons, Derrick
Abstract: Guideline 20 of the updated International Ethics Guidelines for Health‐related Research Involving Humans (2016) by the Council for International Organizations of Medical Sciences (CIOMS) provides guidance on research in disasters and disease outbreaks against the background of the need to generate knowledge quickly, overcome practical impediments to implementing such research, and the need to maintain public trust. The guideline recommends that research ethics committees could pre‐screen study protocols to expedite ethical reviews in a situation of crisis, that pre‐arrangements be made regarding data sharing and biomedical sample sharing, and that sponsors and research ethics committees seek to minimize risk to researchers conducting research during a disaster. This paper critiques these recommendations against the background of the findings of a survey of public health officials and chairs of research ethics committees in the Caribbean during 2016, which sought to determine the best template for the expeditious ethical review of research proposals in emergency and epidemic situations in the Caribbean, and whose findings can serve as a model for other low‐ and middle‐income countries.